(3JCdja aj GdJUhas - (3GdeNJGQ Hf YHO GdLdjd GdJfOZjs
(3ChdgG (B:s
(3hdeG cGf Yde GdJhMjO eHfGg GdfXQ hEjeGf GdMbdO ajg CQOJ Cf CfHg Ydi ZdW ef UQag Yf GdYbd hRYe Cfg dG ESJTgGO EdG HGdfbd , Ke (B~(3CPcQ WQakG ef eYGfi cdeI GdENdGU , de CQ ef Jcde Ydjg bdHi ef Cgd GdEZhGU s
(3BNQgG (B:s
(3hjLdS GdYHO Ydi SQjQ ai gOGjI GdYHGO ajSJNQL GdMceI ef aDGO , hUd jGQH Ydi GdfHi hBdg hUMHg s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeYgO GdehQjJGfi ddHMK GdYdei (B((3JUha (B2932) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs